Rational design and additive manufacture of regenerative vascular grafts: Understanding the interaction between blood cells - surface (2023)
Vascular grafts (VGs) are highly demanded medical devices that replace the function of a blood vessel. Current alternatives use non-degradable materials that elicit a foreign body response, leading to thrombosis and compromising blood flow. As an alternative, Tissue Engineered Vascular Grafts (TEVGs) aim to approach the biological response of native vessels through biodegradability and regenerative potential. Despite the advancements in the development of TEVGs, there are high rates of failure in pre-clinical models, few have entered clinical trials and just 2 are currently on the market. This situation highlights a lack of knowledge in the rational design of TEVGs, which requires a detailed understanding of the mechanisms behind the marked and counterproductive cellular response to the biomaterial surface under physiological flow conditions that led to the failure of current strategies. Tissue regeneration in general and in scaffolds still holds a conundrum due to the complex interplay in the regulation of inflammatory processes affected by the concentration of bioactive molecules, the macro and microstructure of the extracellular matrix, as well as its mechanical properties. For that reason, we decided to take a step back to look at the bigger picture and propose a methodologic pathway to promote advancements in TEVGs going from problem identification to innovative solutions. To this end, we have first performed an extended series of studies and research aiming to identify the current trends in TEVGs and later, the understanding of the mechanisms of cellular interaction with the TEVGs and how it modulates the arterial wall regeneration process. We then transformed this information into design parameters that we could use to improve the overall performance of an ideal TEVG. Finally, we have proposed a final TEVG prototype, our approach, measuring 11 cm in length, 3.0 mm in diameter and 1 mm in thickness, exhibits mechanical properties comparable to native arteries and demonstrates high biocompatibility and hemocompatibility, along with low thrombogenicity rates. And most importantly, it shows promising results to induce and sustain endothelialization with immunomodulatory potential. This study would be the first to report the sequential cascade of processes from inflammation to migration and maturation of vascular wall cells under physiological conditions into the regeneration process of TEVGs and how to overcome the current limitations. Main Objective: Rational engineering of a readily available TEVG that considers the macro and microstructural features of a native artery combined with bioactive molecules inclusion to improve tissue regeneration reducing the need for surgical re-interventions as a result of patency loss and consequent graft failure. Impact: Synthetic VGs are inefficient alternatives in multiple conditions, with 50% losing permeability at 5 years, and requiring costly reinterventions. Despite research on TEVGs, only a few developments have reached the market as a resorbable scaffold with limited use without considering the control of the cellular response. Therefore, the development of our TEVG holds promise as an approach to address the risk factors that affect the longtermprognosis of patients requiring VGs, improving their quality of life and reducing the financial burden on the healthcare system.